An examination of turnaround and organizational performance: the mediating effect of organizational inertia in small and medium enterprises in Malaysia - Muhammad Suhaimi, Mohd Yusof (2021)
The inertia concept apply in the organizational concept but not exhaustively as it emerged from industrial structures and characteristics. The aim of this study is to deploy and develop a research framework to explain the effects of organizational inertia as mediator in Small and Medium Enterprises in Malaysia. The reasons to execute this research are; the concept of organizational inertia is not discuss exhaustively and the current economic turbulent which would cause more harms to SME. SME has less financial budget compare to huge company and tendency to shutdown is higher. The propose framework aims to assist SME to reconsider on turnaround in the organization. The selection of organizational inertia as mediator is to provide clear justification to not implement changes (turnaround) if it is not necessary for organization to execute. Total of 312 Small and Medium Enterprises (SME) involve in the research and this research employ Partial Least Square (PLS) using SMARTPLS 3.27 version. The implication of the study would assist SME to maintain its trajectory rather than change the course which might cause more harms than generate profits to the organization. In conclusion, it indicate the organization must strategize their plans to maintain their survivability during turbulent environment such as pandemic and economic recession. This study recommends further policies development to aid SME in financial perspectives to boost organization and economy growth of the country.